Seroprevalence of hepatitis E virus (HEV) among male craft and manual workers in Qatar (2020–2021) - Nadin, Younes (2023)
BackgroundThe rapid growth of Qatar in the last two decades has attracted a large influx of immigrant craft and manual workers (CMWs) seeking employment in jobs associated with food handling, domestic service, and construction. Nearly 60 % of Qatar's population are expatriates CMWs, including many from hyperendemic countries for HEV. Thus, estimating the seroprevalence of HEV in Qatar and understanding its epidemiology is essential for public health efforts to control HEV transmission in Qatar. MethodsBlood samples from 2670 CMWs were collected between 2020 and 2021. All samples were tested for HEV-IgG antibodies. Positive HEV-IgG samples were tested for HEV-IgM antibodies, and those positives were also tested for viral antigens using an HEV-Ag ELISA kit and HEV-RNA by RT-PCR to confirm current HEV infections. ResultsThe seroprevalence of HEV-IgG was 27.3 % (729/2670; 95 % CI: 25.6–29.0). Of those HEV-IgG positive, 8.23 % (60/729; 95 % CI: 6.30–10.5) were HEV-IgM positive. Of the IgM-positive samples, 2 were HEV-RNA positive (3.39 %; 95 % CI: 0.40–11.7), and 1 was HEV-Ag positive (1.69 %; 95 % CI: 0.04–9.09). In addition, HEV-IgG seroprevalence was associated with age and nationality, with the highest seroprevalence in participants from Egypt (IgG 60.0 %; IgM 5.56 %), Pakistan (IgG 59.0 %; IgM 2.24 %), Nepal (IgG 29.3 %; IgM 2.70 %), Bangladesh (IgG 27.8 %; IgM 2.45 %), and India (IgG 23.9 %; IgM 2.43 %). ConclusionIn this study, we showed that the seroprevalence of HEV among CMWs was slightly higher than what was previously reported among the urban population in Qatar (2013–2016).